Analysis of Fixed Asset Calculation and Management within the Acquisition and Payment Cycle at Kevz Cell - Wahyuni; Aynil Putri; Nurhalisa; Mirnawati; Nurtisatul Mukarramah (www.amertainstitute.com, 2026)
Fixed asset management is an important component of financial reporting for micro and small enterprises, yet systematic recognition, documentation, and depreciation practices remain limited in many businesses. This study aims to analyze the acquisition and payment cycle of fixed assets at Kevz Cell and evaluate its asset management practices against PSAK 16, SAK EMKM, and PMK No. 96/PMK.03/2009. A descriptive qualitative approach was employed, using interviews, observation, and documentation as the primary data collection techniques. The data were analyzed through data reduction, data presentation, and conclusion verification, supported by source and theoretical triangulation. The findings reveal that fixed asset acquisitions at Kevz Cell are conducted through cash payments following price surveys and negotiations; however, purchase receipts are not systematically retained. Consequently, the assets are currently valued based on the owner's subjective estimates rather than verifiable historical acquisition costs. The study also finds that depreciation has never been formally recognized, resulting in an overstatement of reported operating profit. A straight-line depreciation simulation indicates that the estimated accumulated depreciation through 2026 would amount to IDR 101.15 million, reducing the estimated carrying amount of depreciable fixed assets to IDR 120 million. For 2026, the appropriate depreciation expense is estimated at IDR 10.05 million, primarily attributable to the building and fan. These findings demonstrate a substantial gap between current practices and applicable accounting standards. Strengthening transaction documentation, fixed asset registers, and systematic depreciation procedures is therefore essential to improve financial information reliability and support more informed business decisions.